Consanguinity and pregnancy outcomes in a multi‐ethnic, metropolitan European population. (30th September 2014) - Becker, Rolf; Keller, Thomas; Wegner, Rolf‐Dieter; Neitzel, Heidemarie; Stumm, Markus; Knoll, Ute; Stärk, Markus; Fangerau, Heiner; Bittles, Alan
Abstract Objective The aim of the present study was to assess the risk of major anomalies in the offspring of consanguineous couples, including data on the prenatal situation. Methods Over 20 years (1993–2012), 35 391 fetuses were examined by prenatal sonography. In 675 cases (1.9%), parents were consanguineous, with 307 couples (45.5%) related as first cousins, 368 couples (54.5%) beyond first cousins. Detailed information was retrieved on 31 710 (89.6%) fetuses, (consanguineous 568: 1.8%). Results Overall prevalence of major anomalies among fetuses with non‐consanguineous parents was 2.9% (consanguineous, 10.9%; first cousins, 12.4%; beyond first cousins, 6.5%). Adjusting the overall numbers for cases having been referred because of a previous index case, the prevalences were 2.8% (non‐consanguineous) and 6.1% (consanguineous) (first cousin, 8.5%; beyond first cousin, 3.9%). Further adjustment for differential rates of trisomic pregnancies indicated 2.0%/5.9% congenital anomalies (non‐consanguineous/consanguineous groups), that is, a consanguinity‐associated excess of 3.9%, 6.1% in first cousin progeny and 1.9% beyond first cousin. Conclusions The prevalence of major fetal anomalies associated with consanguinity is higher than in evaluations based only on postnatal life. It is important that this information is made available in genetic counselling programmes, especially in multi‐ethnic and multi‐religious communities, to enable couples to make informed decisions. © 2014 John Wiley & Sons, Ltd.